Efektifitas Metode al-Bidayah dalam Peningkatan Kompetensi Santri Pesantren Al-Bidayah di Kabupaten Jember - Fajar Indarsih (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2022)
The challenges and obstacles of Pesantren are increasingly complex with the times. Pesantren can no longer maintain the old ways and methods in socialization, promotion, and teaching and learning systems. One of the Islamic boarding schools that has been transformed in Jember Regency is PP Al-Bidayah. The pesantren managed to find a new method in accelerating students to master the yellow book. The method called the al-Bidayah Method is able to encourage students to be proficient in reading and analyzing the yellow book. The research method uses qualitative with the type of field research. The analysis uses reduction, display, and conclution methods, while the data collection process focuses on the results of interviews and observations. The result of this article review is the urgency of transforming Pesantren formally and in substance, dlohir and mental. In symbolic interactionism theory, it is important to beautify the inside and out. The external appearance of PP Al-Bidayah is in the form of various facilities, facilities and infrastructure. The external appearance of PP Al-Bidayah is in the form of various facilities, facilities and infrastructure. The beautiful appearance of buildings and skyscrapers has implications for people's views to give a positive assessment. If the formal display has been able to hypnotize the public, their response in the form of trust in the PP Al-Bidayah institution is stronger. In addition to the formal look or outer appearance, strengthening the inner look is no less important. PP Al-Bidayah succeeded in grounding the al-Bidayah method which became the forerunner of the transformation of the outer and inner appearance. The al-Bidayah method has proven successful in delivering PP Al-Bidayah students proficiently in reading and analyzing the yellow book. Indicators of the success of the implementation of the al-Bidayah method are also proven by the achievements of students becoming champions in the yellow book competition at the city and provincial levels. With these various achievements, the community must have seen that the PP Al-Bidayah institution has been able to respond to the times with a characteristic is the integration of student science including cognitive, affective, and psychomotor, especially mastery of reading and analyzing the yellow book.